Paternal Involvement and Maternal Perinatal Behaviors: Pregnancy Risk Assessment Monitoring System, 2012-2015. (March 2020) - Kortsmit, Katherine; Garfield, Craig; Smith, Ruben A.; Boulet, Sheree; Simon, Clarissa; Pazol, Karen; Kapaya, Martha; Harrison, Leslie; Barfield, Wanda; Warner, Lee
Objectives: Paternal involvement is associated with improved infant and maternal outcomes. We compared maternal behaviors associated with infant morbidity and mortality among married women, unmarried women with an acknowledgment of paternity (AOP; a proxy for paternal involvement) signed in the hospital, and unmarried women without an AOP in a representative sample of mothers in the United States from 32 sites. Methods: We analyzed 2012-2015 data from the Pregnancy Risk Assessment Monitoring System, which collects site-specific, population-based data on preconception, prenatal and postpartum behaviors, and experiences from women with a recent live birth. We calculated adjusted prevalence ratios (aPRs) and 95% confidence intervals (CIs) to examine associations between level of paternal involvement and maternal perinatal behaviors. Results: Of 113 020 respondents (weighted N = 6 159 027), 61.5% were married, 27.4% were unmarried with an AOP, and 11.1% were unmarried without an AOP. Compared with married women and unmarried women with an AOP, unmarried women without an AOP were less likely to initiate prenatal care during the first trimester (married, aPR [95% CI], 0.94 [0.92-0.95]; unmarried with AOP, 0.97 [0.95-0.98]), ever breastfeed (married, 0.89 [0.87-0.90]; unmarried with AOP, 0.95 [0.94-0.97]), and breastfeed at least 8 weeks (married, 0.76 [0.74-0.79]; unmarried with AOP, 0.93 [0.90-0.96]) and were more likely to use alcohol during pregnancy (married, 1.20 [1.05-1.37]; unmarried with AOP, 1.21 [1.06-1.39]) and smoke during pregnancy (married, 3.18 [2.90-3.49]; unmarried with AOP, 1.23 [1.15-1.32]) and after pregnancy (married, 2.93 [2.72-3.15]; unmarried with AOP, 1.17 [1.10-1.23]). Conclusions: Use of information on the AOP in addition to marital status provides a better understanding of factors that affect maternal behaviors.